Priming app information privacy concerns in mobile ecosystems - Christoph Buck; Simone Burster; Torsten Eymann (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2017)
In the course of experiential computing privacy is entering personal space. Due to the implementation of all kinds of sensors and computing in everyday life of users, their privacy is at high risk. The high risk of privacy is strengthened by the classification of mobile app download decisions in mobile ecosystems as low effort processes. The article follows the call of Dinev et al. (2015) to investigate the influences of behavioral economics on privacy decisions. The paper provides the development of an app information privacy concern and six independent experiments in the field of priming information privacy with altogether 1954 participants. The results support the assumption of app decision-making as low effort process and indicate the influence of priming on individuals' information privacy concerns. This research contributes to increasing importance of understanding individuals' behavior in digital ecosystems.
urn:nbn:de:bvb:703-epub-3419-8
Keywords: 650; Mobile Applications; Information Privacy; Privacy Concerns; Behavioral Economics; Priming